Sintering of Functional Materials - Shishkovsky, Igor (IntechOpen, 2018)
Powder-based materials and treatment technologies rank high in contemporary scientific-technical progress due to their numerous significant technoeconomic qualities. Sintering of such materials allows saving on materials and lowering the cost price of the product, as well as manufacturing complex composite materials with unique combinations of qualities. Materials of record high values of some physic-mechanical and also biochemical characteristics can be obtained owing to structural peculiarities of super dispersed condition. Sintering of functional materials for innovative perspectives in automotive and aeronautical engineering, space technology, lightweight construction, mechanical engineering, modern design, and many other applications requires established relationship in the materials-process-properties system. Therefore, the industry being interested in understanding theoretical modeling, and control over behavior of such powdered materials has promoted the research activities of this manuscript's authors.